Use of TachoSil® patches to prevent pancreatic leaks after distal pancreatectomy: a prospective, multicenter, randomized controlled study. (19th January 2016) - Park, Joon Seong; Lee, Doo‐ho; Jang, Jin‐Young; Han, Youngmin; Yoon, Dong Sup; Kim, Jae Keun; Han, Ho‐Seong; Yoon, YooSeok; Hwang, DaeWook; Kang, Chang Moo; Hwang, Ho Kyoung; Lee, Woo Jung; et al.
Abstract: Background: We performed a prospective, multicenter, randomized controlled study to investigate the clinical outcomes, including postoperative pancreatic fistulas (POPF), after using the TachoSil® patch in distal pancreatectomy (NCT01550406). Methods: Between June 2012 and September 2014, 101 patients at five centers were randomized into Control ( n  = 53) and TachoSil ( n  = 48) groups. In all patients, the pancreas was resected using a stapler with Endo‐GIA™ staples. The TachoSil patch was wrapped around the pancreatic stump only in the TachoSil group, not in Control group. Results: The patient characteristics, including age and diagnosis, were comparable in both groups. The mean operation time (159.4 vs. 172.3 min, P  = 0.081) and postoperative hospital stay (10.0 vs. 9.7 days, P  = 0.279) were similar in the Control and TachoSil groups, respectively. The overall incidence of POPF was 62.4% ( n  = 63). The distribution of grades A, B, and C POPF was similar in the Control ( n  = 14/14/1) and TachoSil ( n  = 23/11/0) groups, as were the overall incidence (54.7% vs. 70.8%, P  = 0.095) and the incidence of grade B and C POPF (28.3% vs. 22.9%, P  = 0.536). Conclusion: This study showed that the TachoSil® patch did not reduce the incidence of POPF after distal pancreatectomy. Abstract : Highlight The authors performed a prospective, multicenter, ramdomized controlled study to investigate the efficacy of TachoSil® patches in preventing pancreatic fistula, the most frequent and serious complication after distal pancreatectomy, for which effective prevention and management methods remain lacking. The patch did not reduce the incidence of postoperative pancreatic fistula.